Smart-Specialization of the Agro-Industrial Complex in the Context of Digital Transformation of Regional Economic Systems - Anna M Kulik; Elena A Lavrinenko; Julia V Lyshchikova; Elena A Stryabkova (Faculty of Economic and Business, 2021)
This article presents a domestic and foreign experience of